THE EFFECT OF SYSTEM QUALITY, INFORMATION QUALITY, SERVICE QUALITY, AND TRAINING QUALITY ON ORGANIZATIONAL PERFORMANCE IN VILLAGE CREDIT INSTITUTIONS (LPD) IN GIANYAR REGENCY - I Kadek Diki Putrawan; Dodik Ariyanto (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The effective implementation of Accounting Information Systems (AIS) plays a crucial role in improving organizational performance, particularly for Village Credit Institutions (LPD), which hold a strategic role in supporting the economic development of traditional village communities. This study aims to analyze the influence of system quality, information quality, service quality, and training quality on organizational performance at LPDs in Gianyar Regency. The research model is based on the Information System Success Model by DeLone and McLean (2003), with an extension by including training quality as an additional variable.This study employs a quantitative approach through a survey method by distributing questionnaires to 78 respondents from 26 eligible LPDs. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the aid of SmartPLS software. The results indicate that all four independent variables—system quality, information quality, service quality, and training quality—have a positive and significant effect on organizational performance.This research contributes theoretically by expanding the information system success model and provides practical implications for LPD managers to enhance the efficiency and effectiveness of financial management through information technology.